A Fluorescent Probe for C24 Fatty Acids to Report the Deep Interior of Lipid Bilayers - Umegawa, Yuichi; Fukunaga, Shiho; Yasuda, Tomokazu; Murata, Michio (Synlett, 2023)
To investigate the interdigitation and the resulting fluctuation of lipid chains in the deep part of biomembranes, we aimed to develop a new fluorescent probe based on the well-known trans-parinaric acid (t-PA), but with a tetraene near the end of the C24 chain. The probe, tetracosa-16,18,20,22-tetraenoic acid (TCTEA), synthesized mainly by means of reported strategies, was found to better reflect the behavior of lipids in the deeper interior of bilayers than did t-PA. TCTEA could serve as a useful probe for studying the plasma-membrane dynamics of very-long-chain fatty acids, which have recently elicited significant attention in relation to necroptosis.
Keywords: long-chain fatty acids; fatty acids; fluorescent probes; teteraenes; lipid bilayers; interdigitation